Notes on the genus Sarmydus Pascoe, 1867 (Cerambycidae: Prioninae: Anacolini) from India with description of a new species - Majumder, Amitava; Drumont, Alain; Bouyer, Thierry; Chandra, Kailash (Zootaxa, 2020)
A new species of Sarmydus Pascoe, 1867, S. bagh sp. nov., is described from north India and adjacent countries based on the habitus of both male and female, and male genitalia characters. Detailed taxonomic investigations reveal previous misidentification of several specimens from India of the new species as S. antennatus Pascoe, 1867. Accordingly, Sarmydus antennatus Pascoe, 1867 is removed from the Indian fauna. Photographs of the holotype of S. antennatus are provided, and the characters of this species discussed in detail. DNA barcoding analysis of the Himalayan Sarmydus species has been done for the confirmation of the new species. This analysis depicts significant genetic divergences of >14% between S. bagh sp. nov. and its congeners, thus, sufficiently supporting morphological interpretations.